Management equity incentives and corporate tax avoidance: Moderating role of the internal control - Wenwu, Xie; Khurram, Muhammad Usman; Qing, Lian; Rafiq, Asia (Frontiers in Psychology, 2023)
Introduction Under the modern enterprise system, the principal-agent relationship can cause a conflict of interest between the two power counterparts, thus affecting the degree of corporate tax avoidance. As a tool to align the interests of management and owners, management equity incentives can alleviate the conflict of interests brought about by the separation of powers and, therefore, may influence corporate tax avoidance. Objectives and methods We examine the relationship between management equity incentives and corporate tax avoidance from both theoretical and empirical perspectives by using data from Chinese A-share listed companies from 2016 to 2020. Firstly, the effect of management equity incentives on tax avoidance is theoretically and normatively analyzed. Secondly, examine the effectiveness of moderating the effect of internal control and distinguishing the ownership of enterprises’ nature through regression analysis. Results (1) There is a positive relationship between management equity incentives and corporate tax avoidance which means, more the stock incentive offered to executives, the more likely corporations are to pursue tax avoidance strategies aggressively. (2) Internal control deficiencies enhance the positive relationship between equity incentives and enterprise tax avoidance behavior. Therefore, in Chinese enterprises, the lack of an internal control system and the failure of internal control measures are prevalent, and such loopholes can intensify the tax avoidance behavior that arises when executives are subject to equity incentives. (3) The influence of management equity incentives on enterprise tax avoidance behavior is greater in state-owned (SOE) than private enterprises. State-owned enterprises are more likely to increase enterprise tax avoidance behavior when management is subject to equity incentives for reasons such as strict performance requirements, lower regulatory oversight, and less interference from negative information. Finally, our findings have significant implications for policymakers/regulators, public companies, investors, standard setters, managerial labor markets, and the welfare of the overall economy.